Adverse childhood experiences and substance abuse in adulthood among Icelandic women - Sandra Friðriksdóttir 1985- (2022)
Background: Previous international studies have indicated an association between adverse childhood experiences (ACEs) and alcohol and other substance abuse in adulthood, and even a dose response relationship between the number of ACEs and alcohol and/or substance abuse. The aim of this study was to investigate whether adverse childhood experiences are associated with current binge drinking and history of substance use disorder among Icelandic women. More specifically, we aimed to investigate this association by number and types of adverse childhood experiences. Methods: Participants consisted of 32,811 women residing in Iceland who took part in a large nationwide population-based study, The Stress and Gene Analysis (SAGA) cohort, in 2018-2019 and answered a web-based questionnaire. The questionnaire included questions about background, having been diagnosed with substance use disorder, adverse childhood experiences (which were assessed with The Adverse Childhood Experience International Questionnaire (ACE-IQ)), and binge drinking during the last year (which was assessed with items from The Alcohol Use Disorder Identification Test (AUDIT)). Logistic regression models were used to obtain odds ratios and 95% confidence intervals to evaluate the association between ten categories of adverse childhood experiences and number of ACEs and substance use disorder and current binge drinking with Icelandic women. Adjustments were made for age, marital status, education, and financial income. Results: Overall, 82% reported at least one adverse childhood experience and 35% had experienced four or more. Participants who experienced four or more ACEs had higher prevalence of having low educational level, low financial income, low social support, being single, and born outside of Iceland than participants who experienced under four ACEs. Our findings suggest an association between ACE score and substance use disorder diagnosis and current binge drinking among Icelandic women, where women who experienced four or more ACEs had the ...